Strategi Meningkatkan Participate Interest Mahasiswa terhadap Program Merdeka Belajar Kampus Merdeka - Ronald, Ronald; Emmerich, Sean (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The education sector is one part of the service industry that has an important role in the development of a country. Data from APTISI (Association of Indonesian Private Universities) in 2021 states that there are more than 4,600 universities in Indonesia, consisting of 32% of State Universities (PTN) and the remaining 68% of Private Universities (PTS). Based on government regulation Permendikbud No. 3 of 2020, in support of increasing the competence of students in higher education, the Merdeka Campus program was formed. One of the private universities participating in the Merdeka Campus program is Pelita Harapan University, Surabaya Campus. The number of samples used in this study was 111 respondents. The sampling method and the sampling technique used were probability sampling and simple random sampling. This study uses a software called AMOS version 22.0 in managing and analyzing data. This study consists of four hypotheses where three hypotheses are accepted and one hypothesis is rejected.